2019
DOI: 10.1002/ijc.32077
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between terminal duct lobular unit features and mammographic density among Chinese breast cancer patients

Abstract: Extensive mammographic density (MD), a well‐established breast cancer risk factor, is a radiological representation of stromal and epithelial breast tissue content. In studies conducted predominantly among Caucasian women, histologic measures of reduced terminal duct lobular unit (TDLU) involution have been correlated with extensive MD, but independently associated with breast cancer risk. We therefore examined associations between TDLU measures and MD among Chinese women, a low‐risk population but with high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Although associations of TDLU involution with age and MD were as expected in our study, we observed a higher proportion of pathology specimens containing TDLUs than prior reports [24,30,31,32]. In contrast to prior reports [31], our population differed in that it was nearly exclusively white and included the highest proportion of obese women.…”
Section: Discussioncontrasting
confidence: 81%
“…Although associations of TDLU involution with age and MD were as expected in our study, we observed a higher proportion of pathology specimens containing TDLUs than prior reports [24,30,31,32]. In contrast to prior reports [31], our population differed in that it was nearly exclusively white and included the highest proportion of obese women.…”
Section: Discussioncontrasting
confidence: 81%
“…The strengths of our study include the application of a computer pathology method to assess breast tissue composition in a large study with rich data on risk factors ( 2 , 3 , 24 , 32 , 33 , 40 ), BBD samples underwent centralized pathology review, and BC cases were confirmed through review of medical records. Some limitations of our study include being underpowered to evaluate the association of breast composition and ER-negative BC, BC molecular subtypes ( 75 , 76 ), or mammographic density ( 77 , 78 ) because mammogram data were available for only 105 women (7.8%) in this study. Our findings were limited to White women, the predominant race of the NHS and NHSII participants.…”
Section: Discussionmentioning
confidence: 99%
“…BBD samples underwent centralized pathology review and breast cancer cases were confirmed through review of medical records. Some limitations of our study include being underpowered to evaluate the association of breast composition and ER negative breast cancer, breast cancer molecular subtypes 71,72 , or mammographic density 73,74 as mammogram data were only available for 105 women (7.8%) in this study. Our findings were also limited to White women, the predominant race of the NHS/NHSII participants.…”
Section: Discussionmentioning
confidence: 99%